What Meaning in a Right to Strike? MedReleaf and the Future of the Agricultural Employees Protection Act - Hastie, Bethany; Farrant, Alex (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2021)
In June 2020, the Ontario Agriculture, Food and Rural Affairs Appeals Tribunal released its decision in UFCW v MedReleaf Phase 2. This decision focused on a constitutional challenge regarding the right to strike under the Agricultural Employees Protection Act, 2002 (AEPA), a separate statutory regime for agricultural workers, who are excluded from the Labour Relations Act, 1995 (LRA) in Ontario. This article explores the right to strike argument as it unfolded in the MedReleaf Phase 2 decision and highlights the enduring tensions that exist in articulating and extending labour rights under subsection 2(d) of the Canadian Charter of Rights and Freedoms to non-Wagner models of labour relations.In particular, we highlight how the arguments and analysis in the MedReleaf Phase 2 decision narrowed the opportunity for a richer examination and interpretation of subsection 2(d) and the AEPA by focusing substantially on a comparison with strike regulation and protections as understood under the LRA. As such, the MedReleaf Phase 2 decision risks interpreting the right to strike under the AEPA as a “bare right” without necessary protections to enable workers to effectively exercise that right. We go on to craft an argument that such protections are readily available to workers under the AEPA. We establish that the language of the AEPA itself, coupled with the subsection 2(d) jurisprudence and fundamental rule of law principles, create the necessary foundation to make a right to strike a meaningful and protected activity under the AEPA. We conclude by offering commentary on the future of striking, and of labour organizing, under the AEPA.